The Role of Motivational Techniques and Strategies Used by Teachers to English Language Classroom at Secondary School Level - Humaira Yousaf (The Indonesian Institute of Science and Technology Research, 2023)
The purpose of this study is to examine the role of motivational techniques employed in secondary school classrooms by public and private school teachers to encourage students. A total of two hundred and forty (240) secondary school teachers from eight public and private schools participated in the study. The information was gathered using a simple sampling approach. A questionnaire was utilized to gather information from teachers to determine how these techniques were implemented in public and private schools. To assess if there was a difference in opinion between the two types of secondary schools, an independent sample t-test was used. The findings found that teachers in both types of schools used a variety of techniques, including cooperative instructional behavior and lesson structuring. Overall work, reading, and writing abilities of students. In addition, private school instructors were more appreciative of students' achievements to motivate them than public school teachers. Teachers at private schools were also found to be more active in encouraging and counseling students to read newspapers than teachers in public schools.